3-D printing for constructing the burr hole ring of lead fixation device in deep brain stimulation. (December 2018) - Chen, Jiazhi; Li, Nanxiang; He, Dian; Wu, Manfeng; Long, Hao; Yang, Kaijun; Qi, Songtao; Zhang, Wangming; Wang, Jun
Highlights: Burr hole ring is of importance in DBS operation. An innovative type of burr hole ring was designed and produced via 3D printing technology. The fixation strength of the innovative burr hole rings is stronger than that of traditional ones in experiments. Abstract: Background: As the bearing structure of fixation device in deep brain stimulation (DBS), burr hole ring is fixed on the skull and used in conjunction with Stimloc and plastic cap. But in patients with traumatic event, excessive movements are likely to bring strain on the anchoring system, which will finally cause the fixation device to fall off from the skull. Method: AutoCAD was used to construct two-dimension (2-D) images for traditional burr hole ring and innovative burr hole ring, respectively. According to the 2-D image, pro/Engineer (Pro/E) will be applied to construct the three-dimension (3-D) geometries. And then, 3-D printing technology was used to build the solid model. These two kinds of burr hole rings were divided into two groups: Innovative group (N = 21) and Traditional group (N = 21). Pull-out strength of these two groups of burr hole rings will be measured by manual tensile force testing machine on the full-size skull model, and the data were transmitted to the notebook in real time for recording and further analyzing. Result: The fixation strength of the innovative group is stronger than traditional group, pull-out strength value of traditional group and innovative group were 34.08 ± 1.31 N and 99.73 ± 2.14 N, respectively. ( P  < 0.001). Conclusion: We provide an innovative burr hole ring, which can fix on the burr hole steadily. Moreover, 3-D printing technology may be suitable for personalized and customized medical treatment in the future.